2018
DOI: 10.1007/s00128-018-2377-6
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Exposure to Tebuconazole Affects Testicular and Epididymal Histomorphometry in Frugivorous Bats

Abstract: This study evaluated the effects of a commercially recommended concentration (1 mL/L) of a fungicide tebuconazole (TBZ) on testicular and epididymal histomorphometry of Artibeus lituratus, following 7 and 30-day oral exposure. TBZ30 bats showed a reduction in the percentage of tubules and seminiferous epithelium, as well as a decrease in tubule and epithelium somatic indexes, and tubular diameter. Inversely, these animals showed increased percentage of intertubular compartment, Leydig cells and blood vessels. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…The correlation and PCA analysis have also indicated that tebuconazole presence may reduce longevity and egg viability in C. elegans. This fungicide toxicity in reproduction has already been reported in different animal models (Guimaraes et al 2018;Li et al 2020;Machado-Neves et al 2018;Fig. 5 Correlation analysis of all data, independent on samples collected pre-or post-pesticide application Fig.…”
Section: Discussionmentioning
confidence: 68%
“…The correlation and PCA analysis have also indicated that tebuconazole presence may reduce longevity and egg viability in C. elegans. This fungicide toxicity in reproduction has already been reported in different animal models (Guimaraes et al 2018;Li et al 2020;Machado-Neves et al 2018;Fig. 5 Correlation analysis of all data, independent on samples collected pre-or post-pesticide application Fig.…”
Section: Discussionmentioning
confidence: 68%
“…Toluidine blue is a metachromatic (a pH-dependent dye that stains cell elements a different color from the dye), staining heparin-containing granules purple or red [ 2 , 63 ]. As a simple, non-sensitive chemical, it can be applied to tissues after various methods of fixation and embedding [ 44 , 46 , 47 , 49 , 50 , 51 , 53 , 55 , 57 , 58 , 61 , 62 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 ]. However, its major disadvantage is the inability to distinguish immature from mature MCs, which could be done by alcian blue-safranin staining [ 45 , 48 , 67 , 72 , 93 ].…”
Section: Mast Cell Detection Methods In the Mammalian Testis And Epid...mentioning
confidence: 99%
“…This study coated papaya with the manufacturer's recommended application concentration of tebuconazole. When great fruit-eating bats (Artibeus lituratus) consumed the fruit, testicular and epididymal histomorphological changes were observed, suggesting that the fungicide tebuconazole may impact reproductive capacities in males [57]. Unfortunately, reproductive females were not evaluated.…”
Section: Reproductionmentioning
confidence: 99%